Keberkesanan Modul Perkembangan Kerjaya Bersepadu terhadap peningkatan motivasi pencapaian pelajar sekolah menengah di Negeri Sembilan - Mohd Noah, Sidek; Jaamat, Mohd Ali (Universiti Putra Malaysia Press, 1998)
The purpose of this study was to test the effectiveness of the Integrated Career Development Module in increasing the achievement motivation amongst secondary school students in Jelebu, Negeri Sembilan. The research design used in this study was the true experimental, pre-test, post-test randomised control group design. The subjects of this study were 50 Form Four students who were divided into three groups using simple random sampling, matching procedure. The groups were an experimental group which was given the treatment using group procedures, another experimental group which was given the treatment using mass procedures and, lastly, the control group. The experimental groups were given the treatment using the the five-phase Integrated Career Development Module formulated by Sidek. All three groups were given the Mehrabian Achievement Scale before and after the treatment. The data collected were then analysed using the two-sample dependent t-test and the ANOVA. The results of this study showed that the Integrated Career Development was effective in increasing achievement motivation among the students. Pertaining to the research findings, several implications and recommendations are put forward.